Scroll, watch, react: Perceived information through multimodality in sludge content on Instagram reels - Dermawan, Muhammad Zaki (Digital Theory, Culture & Society, 2025)
The presence of multimodal culture on social media platforms, primarily on Instagram Reels ground, is composed of disputable perceived information, where comprehended information cannot be instantly sought as a sole interpretation. In the approach of the multimodality concept and engaging in the combination of visual, text, and auditory analyses, which compares plenty of relevant algorithm content, the present research examines the presence of sludge content as one of the various social media content ideas. This paper proposes to define sludge content or split screen video multimodality characters as a mass media technique, particularly on Instagram reels for starring in education, marketing, and entertainment, and how they impact the perceived messages. It discusses whether the presented frames contribute to each other's connections and intentions in constructing the same services. The analysis of the valuation implies that in circumstances where there are multimodal elements in the videos, the two screens intend to serve each other purposes not necessarily the same meaning, but instead support each other with disparate roles in constructing one delivery. The study contends that the appearance of sludge content is not meant to be conceived in only one way. Instead, different individuals might perceive a different sense of understanding, which leads to a varied interpretation or potential misunderstanding.